Prevalence and Risk Factors of Gestational Diabetes Mellitus among Women Attending Antenatal Care in Hadiya Zone Public Hospitals, Southern Nation Nationality People Region - Larebo, Yilma Markos (Biomed Res Int, 2021)
INTRODUCTION: In low- and middle-income countries, gestational diabetes mellitus is increasing globally; it is also a double burden of illness for both mothers and children. While gestational diabetes mellitus is recognized in Ethiopia, according to recent diagnostic criteria, information regarding it remains scarce. OBJECTIVE: To assess the prevalence of gestational diabetes mellitus and associated factors among women attending antenatal care in Hadiya Zone public Hospitals, Southern Ethiopia. METHODS: An institution-based cross-sectional research on a total of 470 pregnant mothers was conducted in the Hadiya Region from August 2019 to December 2020. Finally, via the systematic random sampling process, the study subjects were chosen. A two-hour oral glucose tolerance test of 75 g was used to conduct the universal one-step screening and diagnostic technique. Bivariate and multivariate analyses were used to identify factors associated with gestational diabetes mellitus. RESULTS: Gestational diabetes mellitus prevalence was 26.2% (95% CI, 21.8, 30.5). Urban residents (AOR: 2.181; 95% CI: 1.274, 3.733), primary education (AOR:2.286; 95% CI: 1.396, 3.745), without previous history of abortion (AOR: 0.097; 95% CI: 0.048, 0.196), with history of late gestational age in weeks (29-32) (AOR: 0.393; 95% CI: 0.213, 0.723), with no history of coffee drinking (AOR: 2.704; 95% CI: 1.044, 7.006), and adequate dietary diversity (AOR: 2.740; 95% CI: 1.585, 4.739) were significantly associated with gestational diabetes mellitus. CONCLUSION: In Hadiya Zone public Hospitals, the prevalence of gestational diabetes mellitus among women attending antenatal treatment was higher compared to other studies conducted. The urban residents, primary schooling, no prior history of abortion, late gestational age, no history of coffee drinking, and sufficient dietary diversity were significantly linked with gestational diabetes mellitus. To enhance maternal and child health, reinforcing screening, treatment, and prevention strategies for gestational diabetes mellitus is essential.